Pamana uso pa ba?: Acculturation and the peril of Assimilation to the Surat Mangyan and Ambahan of the Hanunuo-Mangyan of Sitio Calibang, Tanawan and Sinugbuan, Brgy, Panaytayan, Mansalay Oriental Mindoro - De Guzman, Eugene Victoriano (Eximia, 2024)
It is a grand narrative that culture yields identity, but what if the acculturation of a particular indigenous group fails to be balanced? Would it be at the edge of cultural assimilation? This account ends to determine the status quo of the Surat Mangyan and Ambahan of the Hanunuo-Mangyan of Sito Calibang, Tanawan, and Sinugbuan, Brgy. Panaytayan, Masalay Oriental Mindoro. Through an Anthropological inquiry, this paper determined the relevance of Surat Mangyan and Ambahan in conducting their rites and in day-to-day parlance among their small-scale community. It even went further to gauge the knowledge of Hanunuo-Mangyan [of the mentioned Sitios] regarding the nature and significance of Surat Mangyan in their cultural identity. As a kind of Anthropological qualitative research, this paper also discussed some characteristics of culture appropriate to explicate the existing condition of Surat Mangyan and Ambahan. Thus, the nature of this piece is both narrative and expository. By analyzing and interpreting, this paper concluded that while the Hanunuo-Mangyan [of the said Sitios] manage to entertain the culture of Tagalog/English language within their culture viz. language (acculturation), there is a possible threat of assimilation of Ambahan and Surat Mangyan since most of the interviewed Hanunuo-Mangyan asserted that Ambahan and Surat Mangy them have inadequate knowledge of on how to conduct such cultural practices among themselves. Yet, they are fully aware of the significance of Ambahan and Surat Mangyan as cultural treasures.